Exploring Phase Stability and Properties of I‐II2‐III‐VI4 Quaternary Chalcogenides. Issue 8 (25th May 2020) - Shi, Wencong; Khabibullin, Artem R.; Woods, Lilia M.
Abstract: A recently discovered class of quaternary chalcogenides with the I‐II2 ‐III‐VI4 (I = Cu, Ag; II = Zn, Cd; III = Al, Ga, In; VI = S, Se, Te) chemical formula is considered using electronic structure calculations. Through cross‐cation substitution and maintaining the octet rule, these materials can be obtained from the simpler II‐VI zinc blende systems giving five possible structural phases; stannite, kesterite, primitive mixed CuAu, wurtzite‐stannite, and wurtzite‐kesterite. Here, 36 possible chemical compositions are calculated within these phases and the most stable structure is found for each material. By analyzing the lattice parameters, energy band structures, and other characteristics, different property trends of this new class of materials are presented. The electronic properties show that these materials can exhibit semiconductor to semimetal behavior depending on the phase and chemical compositions. Comparisons with other materials from the related I2 ‐II‐IV‐VI4 systems, which are widely explored, allow for further fundamental knowledge of chalcogenide systems to be built and for the exploration of their suitability for practical applications. Abstract : A new class of quaternary chalcogenides with I‐II2 ‐III‐VI4 chemical formula are explored using electronic structure calculations. Thirty‐six possible chemical compositions within five phases are investigated. Comparisons with other materials from the related I2 ‐II‐IV‐VI4 systems, which are widely explored, help to further build fundamental knowledge of chalcogenide systems and to explore their suitability for practical applications.